Envelope and diachronicity in residential energy assessment regulations - Michaux, Maria Celina; Viegas, Graciela Melisa; Blasco-Lucas, Irene Alicia (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
Globally, the residential building stock shows different levels of obsolescence and high energy consumption. Therefore, it is imperative to promote energy savings through measures to improve building efficiency in the rehabilitation and remodeling of housing units. The objective of this work is to analyze the different ways of evaluating energy efficiency through the diachronicity of the renovations introduced during their use, with emphasis on the variations of the building envelope. The method used is a theoretical-qualitative study, structured in two stages that allow addressing the regulatory context in force in 31 countries. It is concluded that the evaluation methods examined apply a synchronic criterion, without considering the dynamics of housing change processes. Together, the regulations of Brazil, Austria, Belgium, Germany, and Cyprus are highlighted for their relevance, potential and approach to the envelope.